Birefringence Variation Independent Fiber-Optic Current Sensor Using Real-Time SOP Measurement - Yinping Liu; Lin Ma; Zuyuan He (IEEE Photonics Journal)
We propose a birefringence variation independent fiber-optic current sensor based on polarization diversity and a real-time state of polarization measurement technique. We theoretically and experimentally demonstrate the compensation for the degradation of Faraday effect due to the variation in birefringence of the sensing fiber. In experiment, a maximally two times higher sensitivity was achieved compared with that of the conventional one. We investigated temperature dependence of proposed method and the observed maximal variation in sensitivity is as small as 6%. The proposed method exhibits good immunity to the random variation of birefringence and the real rotation angle due to the Faraday effect can be accurately detected.